1985
DOI: 10.1159/000183404
|View full text |Cite
|
Sign up to set email alerts
|

Renal Lesions in Sickle Cell Nephropathy in Children

Abstract: Sickle cell nephropathy characterized by proteinuria and predominantly glomerular lesions has not been studied as extensively as renal tubular alterations in sickle cell disease. We reviewed our experience with this entity over a 14-year period. Of 13 children with either proteinuria or the nephrotic syndrome, 8 showed focal and segmental glomerulosclerosis, and 5 had mesangial proliferation. Children with focal and segmental glomerulosclerosis were older at onset of nephropathy and presented with the nephroti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(33 citation statements)
references
References 7 publications
1
32
0
Order By: Relevance
“…19,20 Previous studies have shown similarities in the severity of renal structural and functional changes in SS mice compared with humans with sickle cell disease, including early nephromegaly, glomerular hypertrophy, cortical fibrosis with cyst formation, chronic interstitial nephritis, renal tubular siderosis, and concentrating defects. 4,[21][22][23][24][25] Further studies will be required to establish whether the glomerular lesions are identical to the mesangioproliferative glomerulopathy found in sickle cell disease patients. In this study, several important dissimilarities were noted, including the absence of papillary necrosis and more severe injury to the renal cortex in SS mice than in humans with sickle cell disease.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Previous studies have shown similarities in the severity of renal structural and functional changes in SS mice compared with humans with sickle cell disease, including early nephromegaly, glomerular hypertrophy, cortical fibrosis with cyst formation, chronic interstitial nephritis, renal tubular siderosis, and concentrating defects. 4,[21][22][23][24][25] Further studies will be required to establish whether the glomerular lesions are identical to the mesangioproliferative glomerulopathy found in sickle cell disease patients. In this study, several important dissimilarities were noted, including the absence of papillary necrosis and more severe injury to the renal cortex in SS mice than in humans with sickle cell disease.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that small-molecular-weight proteinuria was found in most of the patients is another set of data against the glomerular involvement. Glomerular diseases have been found in autopsy of patients with thalassemia and have been reported to lead to end-stage renal disease in some [7, 11]. Etiologies such as repeated infection, inability to clear the immune complexes caused by infection and repeated use of desferroxamine have been postulated [7, 9, 30].…”
Section: Discussionmentioning
confidence: 99%
“…Renal involvement has been extensively studied in both Cooley’s disease and sickle cell anemia [1, 2, 3, 4, 5, 6, 7, 8] but sparingly in β-thalassemia/Hb E disease [9, 10]. There are several factors that may adversely affect the kidney in thalassemia: chronic anemia, iron overload, hemosiderosis and oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…1 Many factors could play an important role in the pathogenesis of the disease. It has been shown that 25% of patients with sickle cell disease have proteinuria and the glomerular capillary hypertension may be a pathogenic factor in sickle cell nephropathy.…”
Section: Ahmed Mukhtarmentioning
confidence: 99%